Factors That Influence Interest In Giving Zakat : A Case Study At UPZ Gunadarma University - Nurdiansyah Nurdiansyah; Fikri Zaeni Hasbalah; Siti Aisyah (Jurnal Kajian Akuntansi, Auditing dan Perpajakan, 2024)
The potential of zakat as one part of Islamic philanthropy is quite large, especially in educational institutions, it is interesting to conduct research on the influence of zakat in educational institutions. This study aims to analyze the influence of factors determining the interest of the academic community in giving zakat at UPZ Gunadarma University. This research uses quantitative method with purposive sampling method, the data used is primary data obtained through online questionnaire distribution. The analysis used in this study used multiple linear regression statistical models, t test and f test. The results showed that although the level of zakat literacy and awareness of respondents was quite good, but trust in zakat management institutions (UPZ Gunadarma) was the main factor that drove the decision to give zakat. The low level of trust of some muzakki towards UPZ is a challenge that needs to be overcome so that more academicians are interested in channeling their zakat through UPZ Gunadarma.